2008
DOI: 10.1038/sj.leu.2405101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of the MYST domain histone acetyltransferase TIP60 (HTATIP) as a co-activator of the myeloid transcription factor C/EBPα

Abstract: The transcription factor C/EBPa (CEBPA) is a key player in granulopoiesis and leukemogenesis. We have previously reported the interaction of C/EBPa with other proteins (utilizing mass spectrometry) in transcriptional regulation. In the present study, we characterized the association of the MYST domain histone acetyltransferase Tat-interactive protein (TIP) 60 (HTA-TIP) with C/EBPa. We show in pull-down and co-precipitation experiments that C/EBPa and HTATIP interact. A chromatin immunoprecipitation (ChIP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…We have previously shown that AML1-ETO blocks myeloid transcription factor C/EBPα by downregulating its mRNA, protein, and DNA binding activity in t(8;21) myeloid leukemia [20], and inactivates the myeloid master regulator PU.1 by direct protein-protein interaction in myeloid differentiation [21]. Our group has routinely applied proteomic approach to analyze proteomic profile of various AML subtypes, target, and interacting protein partner identification in AML and APL cells [22][23][24][25][26]. Because AML1-ETO disrupts and blocks the normal function of myeloid transcription factors and requires other cooperating factors to induce leukemia, we hypothesized that the systematic identification of AML1-ETO target proteins on a global proteome-wide level might lead to novel insights into the pathogenesis and systems biology of AML1-ETOinduced leukemia on a post-genomic functional level.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that AML1-ETO blocks myeloid transcription factor C/EBPα by downregulating its mRNA, protein, and DNA binding activity in t(8;21) myeloid leukemia [20], and inactivates the myeloid master regulator PU.1 by direct protein-protein interaction in myeloid differentiation [21]. Our group has routinely applied proteomic approach to analyze proteomic profile of various AML subtypes, target, and interacting protein partner identification in AML and APL cells [22][23][24][25][26]. Because AML1-ETO disrupts and blocks the normal function of myeloid transcription factors and requires other cooperating factors to induce leukemia, we hypothesized that the systematic identification of AML1-ETO target proteins on a global proteome-wide level might lead to novel insights into the pathogenesis and systems biology of AML1-ETOinduced leukemia on a post-genomic functional level.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Bararia et al, 1 published in this issue of Leukemia has brought TIP60, another cellular acetyltransferase under the spotlight of myeloid leukemogenesis. Transcriptional deregulation is a recurring theme in human acute myeloid leukemia (AML).…”
mentioning
confidence: 99%
“…7 To gain further insights into the functional regulation of C/EBPa, Bararia et al have biochemically purified and validated another acetyltransferase, TIP60 as a C/EBPa-interacting partner. 1 They show that TIP60 directly interacts with C/EBPa, and acts as a transcriptional co-activator in an acetyltransferase-dependent manner. TIP60 complexes with C/EBPa to enhance acetylation of histones 3 and 4, and regulates expression of downstream targets including C/EBPa itself ( Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations